On the Inversion of Bessel Ultrahyperbolic Kernel of Marcel Riesz - Darunee Maneetus; Kamsing Nonlaopon (Abstract and Applied Analysis)
We define the Bessel ultrahyperbolic Marcel Riesz operator on the function f by Uαf=RαB*f, where RαB is Bessel ultrahyperbolic kernel of Marcel Riesz, α…C, the symbol * designates as the convolution, and f∈S, S is the Schwartz space of functions. Our purpose in this paper is to obtain the operator Eα=Uα-1 such that, if Uαf=φ, then Eαφ=f.